2010
DOI: 10.1074/jbc.m110.124545
|View full text |Cite
|
Sign up to set email alerts
|

Imaging CREB Activation in Living Cells

Abstract: The Ca 2؉ -and cAMP-responsive element-binding protein (CREB) and the related ATF-1 and CREM are stimulus-inducible transcription factors that link certain forms of cellular activity to changes in gene expression. They are attributed to complex integrative activation characteristics, but current biochemical technology does not allow dynamic imaging of CREB activation in single cells. Using fluorescence resonance energy transfer between mutants of green fluorescent protein we here develop a signal-optimized gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 72 publications
1
31
0
2
Order By: Relevance
“…To improve the specificity of detecting CREB activation by PKGIγ residing in the nucleus, a phospho-CREB biosensor that is localized in the nucleus was employed for these studies. Previously, Friedrich and coworkers showed that a fusion protein consisting of the CREB kinase-inducible domain (KID), a linker, and the CREB-binding protein KID-interaction domain (KIX) sandwiched between an NLS and cyan fluorescent protein (CFP) on the NH 2 -terminal end and yellow fluorescence protein (YFP) on the COOH-terminal (referred to as NLS-ICAP ) exhibited reduced fluorescence resonance energy transfer (FRET) when PKA or calmodulin kinase induced CREB KID phosphorylation and KID-KIX interaction decreased CFP and YFP photonic interaction [35]). Because of the high variation in NLS-ICAP expression observed in the transfected cells during pilot studies, we first analyzed whether the activation of this phospho-CREB biosensor could be detected using fluorescence lifetime imaging microscopy (FLIM) instead of FRET.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To improve the specificity of detecting CREB activation by PKGIγ residing in the nucleus, a phospho-CREB biosensor that is localized in the nucleus was employed for these studies. Previously, Friedrich and coworkers showed that a fusion protein consisting of the CREB kinase-inducible domain (KID), a linker, and the CREB-binding protein KID-interaction domain (KIX) sandwiched between an NLS and cyan fluorescent protein (CFP) on the NH 2 -terminal end and yellow fluorescence protein (YFP) on the COOH-terminal (referred to as NLS-ICAP ) exhibited reduced fluorescence resonance energy transfer (FRET) when PKA or calmodulin kinase induced CREB KID phosphorylation and KID-KIX interaction decreased CFP and YFP photonic interaction [35]). Because of the high variation in NLS-ICAP expression observed in the transfected cells during pilot studies, we first analyzed whether the activation of this phospho-CREB biosensor could be detected using fluorescence lifetime imaging microscopy (FLIM) instead of FRET.…”
Section: Resultsmentioning
confidence: 99%
“…Because cell fixation can affect the efficiency of protein fluorescence, we tested whether NLS-ICAP activation could be detected in formaldehyde-fixed cells using FLIM. In these studies, NLS-ICAP was modulated using forskolin because this had been shown to phosphorylate and modulate FRET of this CREB KID-based biosensor [35]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on this principle, the imaging of the CREB phosphorylation was achieved in living cells by constructing the protein composed of the phosphorylated kinase-induced (KID) and the recognition domain (KIX) sandwitched between the FRET pair. Upon phosphorylation, the KID of CREB binds KIX domain to induce FRET 63. After transfection, the phosphorylation of the construct was comparable to the endogenous CREB phosphorylation and has allowed for measurements in living cells, due to the nontoxicity of the chimeric reporter.…”
mentioning
confidence: 99%